Optimal mechanism for selling two goods - Gregory Pavlov (The University of Western Ontario, Department of Economics, 2010)
We solve for the optimal mechanism for selling two goods when the buyer's demand characteristics are unobservable. In the case of substitutable goods, the seller has an incentive to offer lotteries over goods in order to charge the buyers with large differences in the valuations a higher price for obtaining their desired good with certainty. However, the seller also has a countervailing incentive to make the allocation of the goods among the participating buyers more efficient in order to increase the overall demand. In the case when the buyer can consume both goods, the seller has an incentive to underprovide one of the goods in order to charge the buyers with large valuations a higher price for the bundle of both goods. As in the case of substitutable goods, the seller also has a countervailing incentive to lower the price of the bundle in order to increase the overall demand.
Keywords: C78; D42; D82; L11; 330; multidimensional screening; price discrimination; optimal selling strategies; mechanism design; Marktmechanismus; Verkauf; Preisdifferenzierung; Theorie